Specific Effects of Language Transfer Promoting Teaching and Insights Into the Implementation in EFL-Teaching - Kerstin Göbel; Svenja Vieluf (Karolinum Press, 2018)
The following contribution analyzes language transfer promoting instruction in the context of English as a foreign language (EFL) instruction in 9th grade secondary classes in Germany. By combining data from questionnaires, tests, and video-data, the article sheds light on learning outcomes in the context of language transfer promoting instruction and presents teaching practice of interlanguage reflection in ESL-teaching. Results indicate a positive correlation of language transfer promoting teaching with EFL listening comprehension at the beginning of grade 9. A correlation between language transfer promoting teaching did not show up with text reconstruction. The analysis of selected videos revealed sequences that hint at an attempt to promoting language transfer actually take place in classes of teachers reporting high importance for language transfer promoting teaching. However, these sequences do not display an elaborated language transfer promoting teaching. Language transfer promotion is implemented in a rather implicit way, while referring to German language only. Results indicate the need for elaborated strategies of implementation of language transfer promoting teaching.